Pendampingan Penguatan Literasi Bahasa Inggris Siswa SD YPK Elim Malanu Sorong Melalui Pembelajaran Kooperatif - Yuliana Arsyad; Heriyanti Heriyanti; Andi Musdalifah; Alia Nur Fadhilah; Rinda Hardianti (LP3M Universitas Muhammadiyah Sorong, 2023)
Reading habit must be instilled and developed in children from an early age. Motivating children to read has its own challenges in the midst of such rapid developments. Especially in cultivating the spirit of reading English texts. Educators are expected to have creativity in managing a more creative learning process so that it attracts students to be more motivated to learn. Reading is an important skill that must be possessed by students, so it is considered important to provide assistance to strengthen English reading literacy for students at the elementary school level, so that students get used to reading from an early age. Therefore, the purpose of this community service is to foster a spirit of English literacy in elementary school students. One way to achieve this goal is to use cooperative learning methods, namely studying with groups of four to five people, each adapted to a different level of ability, gender, ethnicity or race. This activity combines smart, easy, fast, and fun learning features. The group learning method is part of the activity implementation methodology. This activity involved YPK Elim Malanu elementary school students, Sorong, Southwest Papua who were in grades two and three. The implementation of this activity takes place from August to December 2021. From the results of this activity it can be concluded that group learning can foster students' interest and enthusiasm in English literacy.